PET Imaging of Neurodegeneration With [18F]AV-1451 PET After Repetitive Traumatic Brain Injury. (1st September 2019) - Mesley, Matthew; Puffer, Ross; Laymon, Charles; Lopresti, Brian; Edelman, Kathryn; Sharpless, Jane; Billigen, Julia; Wilkins, Tiffany; Puccio, Ava; Mathis, Chet; Mountz, James; Okonkwo, David O
Abstract: INTRODUCTION: TBI (traumatic brain injury) is associated with an increased risk of late neurodegeneration in chronic TBI survivors. The underlying pathophysiology of trauma-related neurodegeneration is hypothesized to involve a tauopathy, with p-tau deposited in beta-pleated sheets. Current research focuses on identifying strategies to detect trauma-related neurodegeneration in-Vivo. [F-18]AV-1451, a tau-specific PET radiotracer, may detect hyper-phosphorylated tau deposits in living patients. METHODS: Participants with a history of TBI >6 mo prior with concern for cognitive decline with age-matched controls were recruited. Subjects were classified into three groups: few (=3 TBI exposures), intermediate (4–10 exposures), and numerous (>10 exposures). Participants underwent PET imaging with [F-18]AV-1451, and qualitative and semi-quantitative (SUVR) analyses of radiotracer retention were performed. Visual classification of tau positivity (+/−) was performed with absence of established positivity thresholds for [F-18]AV-1451 SUVR values. All subjects underwent neuropsychological evaluation, including measures of processing speed, executive function, and memory. RESULTS: Twenty-seven TBI subjects and 7 controls were enrolled. A total of 9 participants were categorized as few, 2 as intermediate, 7 as numerous. All TBI subjects demonstrated impairment on at least one neurocognitive measure, while control subjects had normal neuropsychological test results. Analysis of [F-18]AV-1451 uptake patterns demonstrated evidence of tauopathy in 3 subjects, based on visual reads. Significantly increased [F-18]AV-1451 retention was noted in occipital gray matter, posterior cingulate gyrus, and parietal cortex in these 3 tau (+) TBI subjects compared to 24 TBI subjects visually classified as tau (−) and also normal controls. CONCLUSION: Evidence of tauopathy, indicative of trauma-related neurodegeneration, was noted in 3 chronic TBI subjects, all of whom were categorized as numerous (>10) TBI exposures and cognitive deficits on neuropsychological testing. No tau PET [F-18]AV-1451 uptake was noted in control participants or in participants categorized as few or intermediate. The data represent a possible [F-18]AV-1451 PET uptake pattern associated with a clinical neurodegeneration syndrome in repetitive TBI.